Perspective: The Challenge of Clinical Decision-Making for Drug Treatment in Older People. The Role of Multidimensional Assessment and Prognosis - Pilotto, Alberto; Sancarlo, Daniele; Daragjati, Julia; Panza, Francesco (Frontiers in Medicine, 2015)
A complex decision path with a careful evaluation of the risk-benefit ratio is mandatory for drug treatment in advanced age. Enrolment biases in randomized clinical trials (RCTs) cause an underrepresentation of older individuals. In high-risk frail older subjects, the lack of RCTs makes clinical decision-making particularly difficult. Frail individuals are particularly susceptible to adverse drug reactions, and frailty may result in reduced treatment efficacy. Life expectancy should be included in clinical decision-making paths to better assess the benefits and risks of different drug treatments in advanced age. We performed a scoping review of principal hospital- and community-based prognostic indices in older age. Mortality prognostic tools could help clinical decision-making in diagnostics and therapeutics, tailoring appropriate intervention for older patients. The effectiveness of drug treatments may be significantly different in older patients with different risk of mortality. Clinicians need to consider the prognostic information obtained through well validated, accurate, and calibrated predictive tools to identify those patients who may benefit from drug treatments given with the aim of increasing survival.